Pancreatic cancer - Brand, Randall (Henry Stewart Talks, 2016)
General epidemiologic data for pancreatic cancer, Review risk factors for pancreatic cancer, Clinical presentation and diagnostic modalities for pancreatic cancer, Pancreatic cystic lesions, Current status for early detection, diagnosis and staging of pancreatic cancer, Treatment of pancreatic cancer, Current needs: challenges and opportunities, Update interview: Germline and somatic tumor testing for patients with pancreatic adenocarcinoma, Update interview: Determining surgical resectability of a pancreatic adenocarcinoma, Update interview: Neoadjuvant therapy for patients with resectable or borderline-resectable pancreatic adenocarcinoma
Updated at 2020/12/23